The Influence of Customer Satisfaction and Moderation Role of Customer Trust in the Relationship to Customer Loyalty in Digital Banking - Satya Paramadana; Benrik Anthony; M. Fariduddin AZ; Evi Rinawati Simanjuntak (Riviera Publishing, 2025)
This research explores how customer trust influences the connection between satisfaction and loyalty, as reflected in share-of-wallet (SOW) and word-of-mouth (WOM) within the context of digital banking. This is done primarily in Indonesia, where digital banking is flourishing, and the study conducted is scarce. Design/methodology/approach— A quantitative approach was adopted, utilizing purposive sampling to gather responses from 278 Indonesian digital banking users. The PLS-SEM approach was used to analyze the relationships between key variables through structural equation modeling (SEM). Findings - The research revealed that customer satisfaction is significantly affected by factors such as ease of use, service innovation, and the perceived advantages of a product. Additionally, it demonstrated that customer satisfaction significantly affects both the proportion of a customer’s spending and word-of-mouth recommendations. However, contrary to expectations, the study found no evidence that trust moderates the link between satisfaction and share-of-wallet (SAT-SOW) or satisfaction and word-of-mouth (SAT-WOM) within the digital banking sector. Originality/value - This research expands knowledge in the field of digital banking marketing and builds upon prior studies focused on customer-centric service marketing. The study presents a framework that identifies the value associated with SOW and WOM in a modern digital banking service. These findings are beneficial for digital banks, as they can use them to refine their strategies and operations with a customer-centric approach. This, in turn, can help them build lasting, profitable customer relationships and enhance their long-term retention.